Upaya Peningkatan Prestasi Belajar PKN Melalui Metode Pembelajaran Think-Pair-Share (TPS) Bagi Siswa Kelas VII-C UPT SMPN 7 Alla Kabupaten Enrekang Tahun Pelajaran 2019/2020 - Mudjizat Hasan (Jurnal Syntax Transformation, 2022)
The rapid progress of science and technology has resulted in changes in all areas of life. Improving the quality and quality of good education is expected to be able to produce graduates who have high competitiveness to face the tough challenges and competition in the world of work. The purpose of this study was to determine the use of the Think-Pair-Share (TPS) learning method to improve Civics learning achievement in class VII C UPT SMPN 7 Alla in the 2019/2020 school year. This type of research is Classroom Action Research which is carried out in two cycles. The research subjects were students of class VII C UPT SMPN 7 Alla for the academic year 2019/2020, totaling 30 students. Data collection techniques used are tests, observations, questionnaires, interviews, and documentation. The data analysis technique used is an interactive model that has four components, namely data collection, data reduction, data presentation, and drawing conclusions or verification. The results showed that there was an increase in Civics learning achievement in the initial conditions (initial ability test), cycle I, and cycle II. In the initial ability test scores, the average class was only 53.5 with a class completeness of 16.7% and 5 students who scored 70. In the first cycle there was an increase, namely the class average became 69.7 and class completeness increased to 53.3% (an increase of 36.6%) and students who scored 70 were 16 students. Furthermore, in the second cycle also experienced an increase, namely the class average became 81.6 and class completeness became 86.7% (an increase of 33.4%) and the students who scored 70 were 26 students.